ANALYSIS OF EFFECTIVENESS AND EFFICIENCY OF PADANG PUSKESMAS EXPENDITURE BUDGET REALIZATION 2016-2019 - Nisa, Afiatin; Hanifah, Nani (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2020)
The purpose of this study was to determine the Effectiveness of Realized Budget Expenditures at the Padang Health Center and to determine the Realization Efficiency of the Padang Puskesmas Expenditure Budget for the 2016-2019 Budget Year. In the author the method used in research is quantitative. The results of the study showed that the level and criteria for the effectiveness of the expenditure budget realization at the Puskesmas Padang in the 2016-2019 Fiscal Year and 2019 proved effective. For the 2017 Budget Year the effectiveness criteria level proved to be quite effective. The level of efficiency in the Realization of Expenditures at Padang Health Centers in Fiscal Year 2016,2018 and 2019 proved to be efficient. In the 2017 Budget Year the efficiency criteria level proved to be quite efficient.